Quiebrasoles y aleros elaborados con material reciclado para contrarrestar la radiación solar en diseños arquitectónicos innovadores - Sánchez Adrián, Yamil Fernando (2018)
In Guayaquil, several strategists are observed to avoid radiation ranging from arcades and extensive eaves, to different forms of sunblind for control and aesthetics that must meet minimum technical requirements. This research analyzed according to the national and international perspective the parameters that handle the elements of this type, making an inquiry from the technical, aesthetic and functional aspect of the components that assume the challenge of guaranteeing sun protection. An important part of this project was to define a regulation tactic for a building for public use, which contemplates the essential aspects of control and aesthetics, considering the current trends from the weighting of materials, mechanisms, positioning criteria and technical standards, to endorse and conform a quality prototype that meets the efficiency parameters……….